A mutation analysis of the EGFR pathway genes, RAS, EGFR, PIK3CA, AKT1 and BRAF, and TP53 gene in thymic carcinoma and thymoma type A/B3. Issue 5 (3rd October 2019) - Sakane, Tadashi; Murase, Takayuki; Okuda, Katsuhiro; Saida, Kosuke; Masaki, Ayako; Yamada, Takeshi; Saito, Yushi; Nakanishi, Ryoichi; Inagaki, Hiroshi
Abstract : Aims: Thymic carcinoma is rare and usually has a fatal outcome. Gene mutations in the epidermal growth factor receptor (EGFR) signalling pathway and TP53 have not been well analysed in thymic carcinoma. Methods and results: We examined a large cohort of thymic carcinoma and thymoma type A/B3 and looked for gene mutations in the RAS family, EGFR, PIK3CA, AKT1, BRAF and TP53 . Among 54 thymic carcinoma cases, RAS family mutations were detected in 10 cases, EGFR in two, PIK3CA in one, AKT1 in one, BRAF in none and TP53 in five. Among 33 thymoma type A/B3 cases, HRAS gene mutation were found in one, PIK3CA in two and AKT1 in one. All these mutations were those of missense type activating mutations. RAS family mutations were significantly more frequent in thymic carcinoma than in thymoma type A/B3 ( P  = 0.0461). A prognostic analysis focusing on thymic squamous cell carcinoma cases ( n  = 44) showed that the overall survival was significantly shorter in patients with EGFR pathway mutations ( n  = 9) than in those without in a univariate analysis ( P  = 0.0173). Subsequently, EGFR pathway mutations were selected as an independent factor for a poor overall survival in a multivariate analysis ( P  = 0.0389). Conclusions: Mutations in the EGFR pathway and TP53 in thymic carcinoma may be frequent, and the EGFR pathway mutations may be associated with a poor prognosis in thymic squamous cell carcinoma patients. The therapeutic significance of gene mutations in thymic carcinoma should be further clarified.